2020
DOI: 10.1088/1748-9326/ab50a2
|View full text |Cite
|
Sign up to set email alerts
|

A pan-South-America assessment of avoided exposure to dangerous extreme precipitation by limiting to 1.5 °C warming

Abstract: This study investigates the future changes in dangerous extreme precipitation event in South America, using the multi-model ensemble simulations from the HAPPI experiments. The risks of dangerous extreme precipitation events occurrence, and changes in area and population exposure are quantified. Our results show that the likelihood of dangerous extreme precipitation increases in large parts of South America under future warming; changes in extreme precipitation are nonlinear with increasing global mean tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…However, future climate scenarios typically differ less during near‐future periods, so our mid‐century results are likely to occur even if aggressive mitigation policies are pursued in the coming decades. Many open questions result from our analysis including how climate change influences the drivers, character, and prevalence of climatic extremes such as impactful atmospheric river events (Viale et al ., 2018), heat waves (Feron et al ., 2019), drought (Rodrigues et al ., 2019) and other wildfire‐favouring conditions such as downslope windstorms (Abatzoglou et al ., 2020), glacial decline (Braun et al ., 2019), and flood events (Li et al ., 2020). Similarly, ecosystem responses to climate change including the identification of ecoregions that are most susceptible to or most resilient to change [e.g., ‘climate refugia’ ; [Ackerly et al ., 2020)] requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…However, future climate scenarios typically differ less during near‐future periods, so our mid‐century results are likely to occur even if aggressive mitigation policies are pursued in the coming decades. Many open questions result from our analysis including how climate change influences the drivers, character, and prevalence of climatic extremes such as impactful atmospheric river events (Viale et al ., 2018), heat waves (Feron et al ., 2019), drought (Rodrigues et al ., 2019) and other wildfire‐favouring conditions such as downslope windstorms (Abatzoglou et al ., 2020), glacial decline (Braun et al ., 2019), and flood events (Li et al ., 2020). Similarly, ecosystem responses to climate change including the identification of ecoregions that are most susceptible to or most resilient to change [e.g., ‘climate refugia’ ; [Ackerly et al ., 2020)] requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that global aggregate exposure to precipitation extremes is projected to increase in the future (Liao et al, 2019;Chen et al, 2020a), by approximately 2.3% if the temperature increases by 2.0 o C relative to the pre-industry era rather than by 1.5 o C calculated from the CESM simulations (Chen et al, 2020a).…”
Section: Accepted Articlementioning
confidence: 99%
“…However, this value is much greater over the global monsoon regions, in which the 0.5 o C less warming will lead to a population exposure reduction of approximately 25%, as estimated by CMIP5 (Coupled Model Intercomparison Project phase 5) models (Zhang et al, 2018). At the national level, future exposure over China shows a linear upward trend (Zhan et al, 2019;Chen and Sun, 2020) as well as over South America (Li et al, 2020). However, low agreement is reported for the responsibility of these exposure changes, mainly due to the different scenarios and different models used (Liu et al, 2017;Liao et al, 2019;Chen et al, 2020a).…”
Section: Accepted Articlementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, several studies have detected an increasing frequency and intensity of precipitation extremes in the region, mainly during the warm season (Penalba and Robledo, 2010;Cer on et al, 2020;Olmo et al, 2020). Notwithstanding, only few studies have addressed the analysis of future projections of extreme precipitation over SESA, indicating that these changes are expected to be more pronounced during the mid and late 21st century (Sörenssön et al, 2010;Sillmann et al, 2013;Bl azquez and Solman, 2020;Li et al, 2020). For this purpose, it is necessary to first evaluate model performances during the historical period in order to reduce the uncertainty in the projected changes.…”
Section: Introductionmentioning
confidence: 99%